(untitled) (Książnica Śląska, 2025)
The article is devoted to an analysis of stylistic means in assorted stories from a collection titled Insurgenci. Opowiadania o powstaniach śląskich (Insurgents. The stories about The Silesian Uprisings). Among the texts, collected and published by Bolesław Lubosz, a story by Pola Gojawiczyńska, titled Górnoślązaczka [The Upper Silesian woman], is particularly interesting. However, the rest of stories follows the trend of PRL political propaganda and, according to the author, is not attractive for a contemporary reader.